Durable antibody responses elicited by 1 dose of Ad26.COV2.S and substantial increase after boosting: 2 randomized clinical trials. Issue 32 (30th July 2022) - Sadoff, Jerald; Le Gars, Mathieu; Brandenburg, Boerries; Cárdenas, Vicky; Shukarev, Georgi; Vaissiere, Nathalie; Heerwegh, Dirk; Truyers, Carla; de Groot, Anne Marit; Jongeneelen, Mandy; Kaszas, Krisztian; Tolboom, Jeroen; et al.
Highlights: One dose of Ad26.COV2.S elicited high neutralizing and binding antibody levels. Antibody levels persisted through 8 months (neutralizing) and 6 months (binding). A homologous 6-month booster led to a rapid and robust increase in antibody titers. Ad26.COV2.S elicited immune memory supporting anamnestic responses after boosting. Ad26.COV2.S may provide sustained efficacy against reference and variant strains. Abstract: Background: Ad26.COV2.S is a well-tolerated and effective vaccine against COVID-19. We evaluated durability of anti-SARS-CoV-2 antibodies elicited by single-dose Ad26.COV2.S and the impact of boosting. Methods: In randomized, double-blind, placebo-controlled, phase 1/2a and phase 2 trials, participants received single-dose Ad26.COV2.S (5 × 10 10 viral particles [vp]) followed by booster doses of 5 × 10 10 vp or 1.25 × 10 10 vp. Neutralizing antibody levels were determined by a virus neutralization assay (VNA) approximately 8–9 months after dose 1. Binding and neutralizing antibody levels were evaluated by an enzyme-linked immunosorbent assay and pseudotyped VNA 6 months after dose 1 and 7 and 28 days after boosting. Results: Data were analyzed from phase 1/2a participants enrolled from 22 July–18 December 2020 (Cohort 1a, 18–55 years [y], N = 25; Cohort 2a, 18–55y, N = 17; Cohort 3, ≥65y, N = 22), and phase 2 participants from 14 to 22 September 2020 (18–55y and ≥ 65y, N = 73). Single-dose Ad26.COV2.S elicited stable neutralizing antibodies for at least 8–9 months and stable binding antibodies for at least 6 months, irrespective of age. A 5 × 10 10 vp 2-month booster dose increased binding antibodies by 4.9- to 6.2-fold 14 days post-boost versus 28 days after initial immunization. A 6-month booster elicited a steep and robust 9-fold increase in binding antibody levels 7 days post-boost. A 5.0-fold increase in neutralizing antibodies was observed by 28 days post-boost for the Beta variant. A 1.25 × 10 10 vp 6-month booster elicited a 3.6-fold increase in binding antibody levels at 7 days post-boost versus pre-boost, with a similar magnitude of post-boost responses in both age groups. Conclusions: Single-dose Ad26.COV2.S elicited durable antibody responses for at least 8 months and elicited immune memory. Booster-elicited binding and neutralizing antibody responses were rapid and robust, even with a quarter vaccine dose, and stronger with a longer interval since primary vaccination. Trial Registration: ClinicalTrials.gov Identifier: NCT04436276, NCT04535453.